1993
DOI: 10.1017/s0022112093001119
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Rayleigh–Bénard convection: asymmetric modes and vortex states

Abstract: We present optical shadowgraph flow visualization and heat transport measurements of Rayleigh–Bénard convection with rotation about a vertical axis. The fluid, water with Prandtl number 6.4, is confined in a cylindrical convection cell with radius-to-height ratio Γ = 1. For dimensionless rotation rates 150 < Ω < 8800, the onset of convection occurs at critical Rayleigh numbers Rc(Ω) much less than those predicted by linear stability analysis for a laterally infinite system and qualitatively consistent with fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
175
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(203 citation statements)
references
References 32 publications
27
175
0
1
Order By: Relevance
“…[9], with thermal boundary layer effects suppressing Ekman pumping in the core of the vortex and thus leading to formation of a narrow zone of upwelling flow near the core and a ring-shaped downwelling region surrounding it. The structure of the boundary layer vortices may prove important in understanding recent heat transport results which show an enhancement by rotation of the amount of heat transported by convection [6,7]. Previous suggestions on the mechanism for this enhancement have been that Ekman pumping is more effective at extracting heat from the boundary layer than buoyancy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9], with thermal boundary layer effects suppressing Ekman pumping in the core of the vortex and thus leading to formation of a narrow zone of upwelling flow near the core and a ring-shaped downwelling region surrounding it. The structure of the boundary layer vortices may prove important in understanding recent heat transport results which show an enhancement by rotation of the amount of heat transported by convection [6,7]. Previous suggestions on the mechanism for this enhancement have been that Ekman pumping is more effective at extracting heat from the boundary layer than buoyancy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the early roots of these types of investigations in the pioneering theoretical and experimental studies of ChandrasekharLl] and Nakagawa and Frenzen [2], there has been remarkably little quantitative work on the flow structures and in particular the velocity field in rotating convection. The primary tools of past work have been global heat transport measurements, local temperature probes, and qualitative flow visualization with dye, aluminum flakes, streak photography, and shadowgraph [2][3][4][5][6][7]. A semi-quantitative investigation of the vertical temperature structure of a transient thermal plume in the presence of rotation indicated a complex three-dimensional form for non-axially-concentric vortices [8].…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6. Experiments with visualizations [7][8][9][10][11] showed indeed a flow structuring consisting of many columnar vortices. In numerical studies 12,13 these columnar vortices were also observed.…”
Section: Introductionmentioning
confidence: 95%
“…However, at modest rotation rates, experiments [9][10][11] and numerical simulations [12][13][14][15] have shown that under certain conditions the heat transport can also be enhanced, before it rapidly decreases for stronger rotation. This enhancement has been ascribed to Ekman pumping [13,[16][17][18]: Because of the rotation, rising or falling plumes of hot or cold fluid are stretched into vertical vortices that suck fluid out of the thermal boundary layers (BL) adjacent to the bottom and top plates.…”
mentioning
confidence: 99%